Influence of Parental Psychological Flexibility on Pediatric COVID-19 Vaccine Hesitancy: Mediating Role of Self-Efficacy and Coping Style - Wang, Yongyi; Zhang, Xinping (Frontiers in Psychology, 2021)
Background: Pediatric COVID-19 vaccine hesitancy hinders the establishment of immune barrier in children. Psychological flexibility may be a key contributing factor to pediatric COVID-19 vaccine hesitancy, and self-efficacy and coping style play an important role in the relationship, but the underlying mechanisms remain unknown. Methods: A cross-sectional study was conducted on parents from June 2021 to July 2021. A total of 382 parents were recruited for an online-investigation. Serial mediation models were used to examine whether self-efficacy and coping style mediated in the psychological flexibility-pediatric COVID-19 vaccine hesitancy linkage. Result: Psychological flexibility was negatively related to pediatric COVID-19 vaccine hesitancy (r=-0.198, P<0.001). Coping styles rather than self-efficacy played a mediating role independently (95%CI: -0.263 to -0.058). Serial mediation analyses indicated that s elf-efficacy and coping style co-play a serial mediating role in the association of psychological flexibility and pediatric COVID-19 vaccine hesitancy (95%CI: -0.037 to -0.001). Conclusion: The present study showed that high psychological flexibility, high self-efficacy and positive coping style were conducive to the lower pediatric COVID-19 vaccine hesitancy.